Enterprise Resource Planning of Procurement Process with SAP MM Module - Dhuhadmya Anggiya Kirana; Muhardi Saputra; Warih Puspitasari (International Journal of Innovation in Enterprise System, 2021)
PT XYZ is one of the mining companies in Indonesia that has many subsidiaries. From user interviews, there’s a problem in carrying out daily transactions in the procurement process. There is no integration between departments when using existing applications, lots of inappropriate data, and some documents with missing files. Thus causing data not on time and working time. The analysis was carried out using a conceptual model to see the problems and needs in PT XYZ. ERP system needs to be implemented, coordinating the company’s business processes and reset the company’s infrastructure and standardization. The ERP system in the material management module will be implemented using the ASAP method because this method is tailored to the company. The ASAP method can describe implementation activities to support project management and data migration faster than other implementation methods.